Physical and Sexual Violence Predictors: 20 Years of the Women’s Interagency HIV Study (WIHS) Cohort - Decker, Michele R. (Am J Prev Med, 2016)
INTRODUCTION: Gender-based violence (GBV) threatens women’s health and safety. Few prospective studies examine physical and sexual violence predictors. Baseline/index GBV history and polyvictimization (intimate partner violence, non-partner sexual assault, and childhood sexual abuse) were characterized. Predictors of physical and sexual violence were evaluated over follow-up. METHODS: HIV-infected and uninfected participants (N=2,838) in the Women’s Interagency HIV Study (WIHS) provided GBV history; 2,669 participants contributed 26,363 person years of follow-up from 1994 to 2014. In 2015–2016, multivariate log-binomial/Poisson regression models examined violence predictors including GBV history, substance use, HIV status, and transactional sex. RESULTS: Overall, 61% reported index GBV history; over follow-up, 10% reported sexual and 21% reported physical violence. Having experienced all three forms of past GBV posed greatest risk (adjusted incidence rate ratio [AIRR](physical)=2.23, 95% CI=1.57, 3.19; AIRR(sexual)=3.17, 95% CI=1.89, 5.31). Time-varying risk factors included recent transactional sex (AIRR(physical)=1.29, 95% CI=1.03, 1.61; AIRR(sexual)=2.98, 95% CI=2.12, 4.19), low income (AIRR(physical)=1.22, 95% CI=1.01, 1.45; AIRR(sexual)=1.38, 95% CI=1.03, 1.85), and marijuana use (AIRR(physical)=1.43, 95% CI=1.22, 1.68; AIRR(sexual)=1.57, 95% CI=1.19, 2.08). For physical violence, time-varying risk factors additionally included housing instability (AIRR=1.37, 95% CI=1.15, 1.62); unemployment (AIRR=1.38, 95% CI=1.14, 1.67), exceeding seven drinks/week (AIRR=1.44, 95% CI=1.21, 1.71), and use of crack, cocaine, or heroin (AIRR=1.76, 95% CI=1.46, 2.11). CONCLUSIONS: Urban women living with HIV and their uninfected counterparts face sustained GBV risk. Past experiences of violence create sustained risk. Trauma-informed care, and addressing polyvictimization, structural inequality, transactional sex, and substance use treatment, can improve women’s safety.